Protocol for a systematic review and meta-analysis on the effects of cold-water exposure on mental health - Steven Schepanski; Steven Schepanski; Florian Batta; Florian Batta; Marleen Schröter; Marleen Schröter; Georg Seifert; Georg Seifert; Anna Katharina Koch; Anna Katharina Koch (Frontiers in Psychiatry)
Cold-water exposure has gained increasing popularity as a self-applied intervention for improving mental health and psychological well-being. While anecdotal evidence and popular media suggest potential benefits for reducing stress, anxiety, and depressive symptoms, the scientific evidence supporting these claims remains fragmented. This protocol outlines the methodology for a systematic review and meta-analysis aiming to critically appraise and synthesize the available evidence on the effects of CWE on mental health outcomes in adult populations, including both healthy individuals and those with clinical conditions. The review will examine both psychological variables and physiological stress markers in response to cold-water exposure interventions. Following PRISMA 2020 guidelines, a systematic search will be conducted in PubMed, PsycINFO, Embase, and Web of Science. Eligible studies will include randomized controlled trials, controlled clinical trials without randomization, cohort studies, and case-control studies. Risk of bias will be assessed using RoB1 for randomized controlled trials, ROBINS-I for non-randomized intervention studies, and ROBINS-E for observational studies. Random-effects meta-analyses will be conducted where sufficient data are available. The review will provide a structured quantitative synthesis of cold-water exposure’s effects on mental health, helping to bridge the gap between popular claims and empirical evidence. The findings will inform future research, public health guidelines, and the development of safe and effective cold-water exposure protocols for clinical and wellness applications.